Determining the type of explosive item using a decision tree - Kazhan, D.V.; Levytska, T.O.; Kryvenko, O.V. (Reporter of the Priazovskyi State Technical University Section Technical sciences, 2023)
The present circumstances in Ukraine delineate specific areas of study. The imperative to identify an explosive device is increasingly paramount for adults and particularly for children. Failing to recognize this danger poses a threat to health and life. The paper presents a decision tree method for classifying the type of explosive objects. This allows you to draw conclusions about the type of explosive object hidden depending on the type of soil. This problem is relevant, as it allows to reasonably explain the type of danger depending on various external factors. The paper offers a general representation of the construction of a decision tree for determining the type of explosive objects. In addition, the work provides a visualization of the division into nodes for a visual representation of the construction of a decision tree, taking into account the division into subtrees and nodes. The nodes are the main attributes: voltage, sensor height above ground level, soil type. The decision tree construction algorithm and the structural block diagram of the ID3 algorithm are given. A study was conducted based on who was chosen to measure the entropy decision tree split chaos. The main characteristics of the ID3 algorithm were listed, taking into account the subject area in which it is used. The paper presents one of the built decision trees, which was built as part of research to determine the type of explosive object depending on the possible type of soil, for example, it is dry and sandy soil. Moreover, the paper provides a comparative analysis of the decision tree model against existing methodologies, shedding light on its efficacy, accuracy, and potential advancements in enhancing threat detection capabilities. This comprehensive analysis not only showcases the model's strengths but also offers insights into potential areas for refinement and improvement В роботі наведено метод дерева рішень для класифікації типу вибухонебезпечних предметів. Це дозволяє робити висновки відносно типу вибухонебезпечного предмету, що заховано в залежності від типу ґрунту. Дана проблематика є актуальною, оскільки дозволяє обґрунтовано пояснювати тип небезпеки в залежності від різних зовнішніх факторів. В роботі запропоновано загальне представлення побудови дерева рішень для визначення виду вибухонебезпечних предметів. Крім цього в роботі надано візуалізацію розбиття на вузли для наочного представлення побудови дерева рішень з урахуванням розбиття на піддерева та вузли. У якості вузлів виступають основні атрибути: напруга, висота датчика над рівнем ґрунту, тип ґрунту. Наведено алгоритм побудови дерева рішень та структурну блок-схему алгоритму ID3. Було проведено дослідження, на основі якого було обрано для вимірювання хаосу розбиття дерева рішень ентропію. Були перелічені основні характеристики алгоритму ID3 з урахуванням предметної галузи, в якій він застосовується. В роботі наведено одне з побудованих дерев рішень, що було побудовано в рамках досліджень для визначення типу вибухонебезпечного предмета в залежності від можливого типу ґрунту, на прикладі це сухий та піщаний ґрунт